PENGARUH EDUKASI PEMBATASAN CAIRAN TERHADAP PENCAPIAN DRY WEIGHT PADA PASIEN HEMODIALISIS - Ramadhani; Silaen, Harsudianto; Tarihoran, Yusrial; Hasibuan, Muhammad Taufik Daniel (Jurnal Keperawatan Priority, 2020)
Fluid status in patients with renal failure can determine fluid adequacy and subsequent fluid therapy. Dry weight is weight without excess fluid formed after the dialysis action or the lowest weight that is safe to reach the patient after dialysis. The purpose of this study was to determine the effect education about fluid restriction on dry weight pre intra and post hemodialysis ignition at Murni Teguh Memorial Hospital. Progressive and irreversible impairment of renal function in which the body's ability to fail to maintain metabolism and fluid and electrolyte balance, causing uremia (retention of urea and other nitrogenous waste in the blood) which can cause chronic kidney failure.  The design of this research is quasi-experiment without control pre and post-test design. Sampling in this study were patients undergoing regular hemodialysis, totaling 58 people, using purposive sampling technique. The results of the study obtained the effect of education about fluid restriction on dry weight ignition in regular hemodialysis patients at Murni Teguh Memorial Hospital Medan obtained p-value 0.007<0.05. It is recommended that nurses increase the frequency of health education about the fluid needs of hemodialysis patients and problems that arise during hemodialysis, and improve their skills in determining the right dry weight.